PENGARUH PENETAPAN HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN PADA TOKO BATA METROPOLITAN CITY PANAM PEKANBARU - Novia Khoirunnisa; mashur Padli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the effect of pricing and service quality on consumer buying interest at brick shops in the metropolitan city of pekanbaru. The methods in this research is descriptive and quantitative statistics with analitycal methods. In this research is multiple analysis. The sample in this study amounted to 100 respondents who were determined using random sampling technique and using questionnaires as data collection. The research results show that pricing (X1) has a significant positive effect on consumer buying interest (Y). Service quality (X2) has a significant positive effect on consumer buying interest (Y). And pricing (X1) quality of service (X2) has a significant effect. Significantly simultaneously on consumer buying interest (Y) at the brick shop in the metropolitan city of pekanbaru. Keywords : Pricing, Service Quality, And Consumer Buying Interest.